Impact of antiepileptic drugs therapy on thyroid profile in epileptic patients of Punjab origin - Singh, Kuldip; Kaur, Harleen (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Epilepsy requires lifelong therapy with antiepileptic drugs (AEDs) and having medical and psychological consequence. So, the present study was conducted to evaluate the role of different AEDs on thyroid profile in epileptic patients. Methods: 50 epileptic patients receiving AEDs for minimum 1 year were recruited as study group and 50 healthy subjects considered as control group. These subjects were recruited from general (rural or urban) community of Punjab. Fasting blood samples were drawn from patients and healthy subjects for the evaluation of triiodothyronine (T3), thyroxine (T4) and thyroid stimulating hormone (TSH) levels. Results: Significant increase in TSH levels were recorded in epileptic patients while no significant change was found in T3 and T4 epileptic patients treated with different AEDs with respect to healthy controls. Maximum increase in TSH was seen in phenytoin, treated epileptic patients and maximum fall in TSH was recorded in levetiracetam treated epileptic patients. Maximum increase in T3 and T4 levels was found in phenytoin while a maximum decrease was recorded T3 and T4 levels in carbamazepine treated epileptic patients in comparison to other drugs treated patients. Conclusions: Aforementioned observations suggested that epileptic patients treated with phenytoin, valproic acid, carbamazepine and levetiracetam for long time could cause initiation of subclinical hypothyroidism further could leads to overt hypothyroidism which in turn responsible for pathophysiology of various coronary heart disease. Routine screening of thyroid profile during chronic use of AEDs is recommended.